Optimizing Analog Identification and Evaluation in the OECD QSAR Toolbox to Enable Robust Read-Across - E. Byrd; C. Albertson; P. Kern; L. Reinsalu; J. Rose; G. Yan; X. Zhang; C. Lester (Regulatory Toxicology and Pharmacology, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

Love bites? Pre-copulatory behaviours of whale sharks (Rhincodon typus) at Ningaloo Reef, Western Australia - Christine Barry; Emily Lester; Micheal P. Doane; Luciana C. Ferreira; Michele Thums; Adrian C. Gleiss; Mark G. Meekan (Frontiers in Marine Science, 2025)
Very little is known about the reproductive behaviours of whale sharks ( Rhincodon typus ). Here, we describe field observations of courtship behaviour by a whale shark at Ningaloo Reef, Western Australia. We witnessed and recorded following and biting behaviours by a sexually mature male of a smaller female. Following and biting are common events during courtship and copulation of other species of elasmobranchs. Our observations are consistent with earlier reports of courting behaviours in whale sharks provided by fishers, the pilot of a light plane and observations of courtship by a sexually mature male towards females held in aquaria.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The effects of stem bromelain on the gelation behavior of kappa carrageenan under linear and nonlinear rheological regimes - Wilfred V. Rios; Lester C. Geonzon; Arlyn M. Roque; Ma Roxan B. Abiquibil; Mary Diane A. Pilapil; Mark Adones P. Lingaro; Hyacinth N. Suarez; Raymund Lee Antonio C. Sarmiento; Shingo Matsukawa; Rommel G. Bacabac (Food Hydrocolloids, 2024)

Microrheological properties and local structure of ι-carrageenan gels probed by using optical tweezers - Lester C. Geonzon; Motoyoshi Kobayashi; Manlio Tassieri; Rommel G. Bacabac; Yasuhisa Adachi; Shingo Matsukawa (Food Hydrocolloids, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New data on Henneguya postexilis Minchew, 1977, a parasite of channel catfish Ictalurus punctatus, with notes on resolution of molecular markers for myxozoan phylogeny - Ethan T. Woodyard; Thomas G. Rosser; Justin M. Stilwell; Alvin C. Camus; Lester H. Khoo; Geoffrey Waldbieser; W. Walter Lorenz; Matt. J. Griffin (Systematic Parasitology, 2022)

Asthma and high-intensity interval training have no effect on clustered cardiometabolic risk or arterial stiffness in adolescents - M. A. McNarry; L. Lester; E. A. Ellins; J. P. Halcox; G. Davies; C. O. N. Winn; K. A. Mackintosh (European Journal of Applied Physiology, 2021)
Purpose Cardiometabolic risk, including arterial stiffness, is increasing in youth. Those with asthma are suggested to be particularly at risk of cardiovascular disease. Efficient and effective strategies are required to prevent the atherosclerotic process in youth. The purpose of this study was to investigate the effect of 6 months high-intensity interval training (HIIT) on cardiometabolic risk in youth with and without asthma. Methods 65 adolescents (31 mild asthma; 34 non-asthma) were recruited, 32 (16 asthma) of whom were randomly allocated to receive HIIT three times per week for 6 months. At baseline, mid-intervention, post-intervention and at a 3-month follow-up, anthropometric, metabolic and vascular determinants of cardiometabolic risk were assessed. Following principal component analysis (PCA), linear mixed models were used to assess the influence of asthma, HIIT and their interaction. Results Seven factors were identified which explained 88% of the common variance shared among the parameters. Those with asthma demonstrated lower arterial stiffness factor scores mid-intervention ( P = 0.047) and lower cholesterol factor scores post-intervention ( P = 0.022) but there was no effect of the intervention, or interaction effects, on any PCA-identified factor, at any time-point. HIIT was associated with a lower low-density lipoprotein and diastolic blood pressure at mid-intervention. Discussion Neither arterial stiffness nor clustered cardiometabolic risk are influenced by HIIT in adolescents with or without asthma, despite important changes in blood lipid and pressure profiles. Blood pressure, augmentation and pulse wave velocity should be considered physiologically distinct constructs and as potential markers of cardiovascular health.

Asymptotic Growth of Whale Sharks Suggests Sex-Specific Life-History Strategies - Mark G. Meekan; Brett M. Taylor; Emily Lester; Luciana C. Ferreira; Ana M. M. Sequeira; Alistair D. M. Dove; Matthew J. Birt; Alex Aspinall; Kim Brooks; Michele Thums (Frontiers in Marine Science, 2020)

Tracking Improvement in Simulated Marine Biogeochemistry Between CMIP5 and CMIP6 - Roland Séférian; Sarah Berthet; Andrew Yool; Julien Palmiéri; Laurent Bopp; Alessandro Tagliabue; Lester Kwiatkowski; Olivier Aumont; James Christian; John Dunne; Marion Gehlen; Tatiana Ilyina; et al. (Current Climate Change Reports, 2020)
Purpose of Review The changes or updates in ocean biogeochemistry component have been mapped between CMIP5 and CMIP6 model versions, and an assessment made of how far these have led to improvements in the simulated mean state of marine biogeochemical models within the current generation of Earth system models (ESMs). Recent Findings The representation of marine biogeochemistry has progressed within the current generation of Earth system models. However, it remains difficult to identify which model updates are responsible for a given improvement. In addition, the full potential of marine biogeochemistry in terms of Earth system interactions and climate feedback remains poorly examined in the current generation of Earth system models. Summary Increasing availability of ocean biogeochemical data, as well as an improved understanding of the underlying processes, allows advances in the marine biogeochemical components of the current generation of ESMs. The present study scrutinizes the extent to which marine biogeochemistry components of ESMs have progressed between the 5th and the 6th phases of the Coupled Model Intercomparison Project (CMIP).

Equine Pulmonary Cryptococcosis: A Comparative Literature Review and Evaluation of Fluconazole Monotherapy - C. J. Secombe; G. D. Lester; M. B. Krockenberger (Mycopathologia, 2017)

Four putative entomopathogenic fungi of armoured scale insects on Citrus in Australia - Hang Thi Dao; G. Andrew C. Beattie; Amy Y. Rossman; Lester W. Burgess; Paul Holford (Mycological Progress, 2016)

Systematics and biology of two species of Microcera associated with armoured scales on citrus in Australia - Hang Thi Dao; G. Andrew C. Beattie; Amy Y. Rossman; Lester W. Burgess; Paul Holford (Mycological Progress, 2015)

Predicting the likely response of data‐poor ecosystems to climate change using space‐for‐time substitution across domains - Rebecca E. Lester; Paul G. Close; Jan L. Barton; Adam J. Pope; Stuart C. Brown (Global Change Biology, 2014)
Predicting ecological response to climate change is often limited by a lack of relevant local data from which directly applicable mechanistic models can be developed. This limits predictions to qualitative assessments or simplistic rules of thumb in data‐poor regions, making management of the relevant systems difficult. We demonstrate a method for developing quantitative predictions of ecological response in data‐poor ecosystems based on a space‐for‐time substitution, using distant, well‐studied systems across an inherent climatic gradient to predict ecological response. Changes in biophysical data across the spatial gradient are used to generate quantitative hypotheses of temporal ecological responses that are then tested in a target region. Transferability of predictions among distant locations, the novel outcome of this method, is demonstrated via simple quantitative relationships that identify direct and indirect impacts of climate change on physical, chemical and ecological variables using commonly available data sources. Based on a limited subset of data, these relationships were demonstrably plausible in similar yet distant (>2000 km) ecosystems. Quantitative forecasts of ecological change based on climate‐ecosystem relationships from distant regions provides a basis for research planning and informed management decisions, especially in the many ecosystems for which there are few data. This application of gradient studies across domains – to investigate ecological response to climate change – allows for the quantification of effects on potentially numerous, interacting and complex ecosystem components and how they may vary, especially over long time periods (e.g. decades). These quantitative and integrated long‐term predictions will be of significant value to natural resource practitioners attempting to manage data‐poor ecosystems to prevent or limit the loss of ecological value. The method is likely to be applicable to many ecosystem types, providing a robust scientific basis for estimating likely impacts of future climate change in ecosystems where no such method currently exists.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Stock discrimination and movements of narrow‐barred Spanish mackerel across northern Australia as indicated by parasites - B. R. Moore; R. C. Buckworth; H. Moss; R. J. G. Lester (Journal of Fish Biology, 2003)
The parasite fauna of Spanish mackerel Scomberomorus commerson from 10 sites across northern Australia and one site in Indonesia, was examined to evaluate the degree of movement and subsequent stock structure of the fish. Kupang fish (Indonesia) had very few Terranova spp., Grillotia branchi , Otobothrium cysticum or Pterobothrium sp. compared to Australian fish, indicating that no Australian fish enter the Kupang fishery. Univariate and discriminant function analysis of four ‘temporary’ parasite species, the copepod Pseudocycnoides armatus and the monogeneans Gotocotyla bivaginalis , Pricea multae and Pseudothoracocotyla ovalis , demonstrated little similarity between areas of northern Australia, indicating minimal short‐term exchange between neighbouring groups of S. commerson . Analyses of five ‘permanent’ parasite species, the larval helminths G. branchi , O. cysticum , Pterobothrium sp., Callitetrarhynchus gracilis and Paranybelinia balli , also revealed large differences between areas thus indicating long‐term separation. There are at least six parasitological stocks across northern Australia: Fog Bay/Bathurst Island, Cape Wessel, Groote/Sir Edward Pellew, Mornington Island, Weipa, and the Torres Strait. The occurrence of a few irregular fish in the samples suggested that up to 5% of fish moved between stocks during their lifetime. The similarity of within‐school variability to that between schools showed that the fish do not form long‐term school associations.

Interaction of Formaldehyde with Soil Humic Substances: Separation by GFC and Characterization by 1 H-NMR Spectroscopy - C. M. Cooke; N. J. Bailey; G. Shaw; J. N. Lester; C. D. Collins (Bulletin of Environmental Contamination and Toxicology, 2003)

Movement and stock structure of narrow‐barred Spanish mackerel as indicated by parasites - R. J. G. Lester; C. Thompson; H. Moss; S. C. Barker (Journal of Fish Biology, 2001)
Data from permanent parasites (juvenile trypanorhynchs and anisakids) indicated that Spanish mackerel Scomberomorus commerson from four sites on the west coast of Australia, Abrolhos. Shark Bay, Exmouth and Onslow, intermingled and were probably all drawn from the same stock. Fish from Broome, Kupang (Indonesia), Groote Eylandt‐Torres Strait and the east coast of Australia had distinct faunas of permanent parasites and probably each belonged to a different stock. There was evidence of movement of fish between Broome and the west coast. Abundances of temporary parasites (gill copepods and monogeneans) suggested that males and females on the west coast migrated separately because in several cases the parasite fauna of one sex was more similar to that offish in an adjacent area than to the opposite sex in the same area.

AFLP analysis of genetic relationships in the tribe Datureae (Solanaceae) - E. S. Mace; C. G. Gebhardt; R. N. Lester (Theoretical and Applied Genetics, 1999)

AFLP analysis of genetic relationships among the cultivated eggplant, Solanummelongena L., and wild relatives (Solanaceae) - E. S. Mace; R. N. Lester; C. G. Gebhardt (Theoretical and Applied Genetics, 1999)

Mercuty in Precipitation and Its Relation to Bioaccumulation in Fish: A Literature Review - S. G. Downs; C. L. MacLeod; J. N. Lester (Water, Air, & Soil Pollution, 1998)

Coronavirus-like particles in nonhuman primate feces - G. C. Smith; T. L. Lester; R. L. Heberling; S. S. Kalter (Archives of Virology, 1982)